Evaluating Student Competency Outcomes under the ALMAUN Active Learning Curriculum: An Empirical Study in Non-Formal Qur’anic Education - Bambang Wahrudin; Dian Kristina; Desriyanti Desriyanti; Amelia Puspita (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
The global transition toward competency-based and outcome-oriented education has highlighted the importance of curriculum models that integrate clearly defined learning outcomes, systematic learning progression, and authentic assessment. However, empirical evidence regarding the evaluation of competency-based curricula within non-formal Qur’anic educational settings remains limited. This study aimed to evaluate the effectiveness of the ALMAUN curriculum in developing multidimensional Islamic competencies among students across different educational levels. A quantitative evaluative study employing a cross-sectional ex post facto design was conducted with 105 students from four levels of Qur’anic education, namely PAUDQu (n = 20), TKA (n = 44), TPA (n = 25), and TQA (n = 16) at Muhammadiyah Ponorogo Al-Qur’an Education Park, Indonesia. Data were collected through the Islamic Competency Assessment Sheet, which assessed Qur’anic reading, short surah memorization, Hadith memorization, daily prayers, practical worship, Arabic literacy (khat and imla’), and mahfudzat, and were analyzed using descriptive statistics, One-Way ANOVA, and Tukey’s HSD post hoc test. The findings revealed that the ALMAUN curriculum effectively facilitated the progressive development of students’ Islamic competencies, with TQA students demonstrating significantly higher overall achievement than students at lower educational levels, and all TQA students attaining the highest competency category (Mumtaz). The results further indicate that a structured, sequential, competency-based curriculum supported by authentic performance assessment contributes to the development of holistic religious competencies, although Arabic literacy competencies remain an area requiring pedagogical improvement. This study contributes to the international discourse on competency-based Islamic education by providing empirical evidence that integrating constructive alignment and authentic assessment can enhance curriculum effectiveness in non-formal Qur’anic education. The findings offer practical implications for designing competency-oriented Islamic curricula that promote comprehensive religious competency development and sustainable quality improvement.